β2-integrins control HIF1α activation in human neutrophils - Kling, Lovis; Eulenberg-Gustavus, Claudia; Jerke, Uwe; Rousselle, Anthony; Eckardt, Kai-Uwe; Schreiber, Adrian; Kettritz, Ralph (Frontiers in Immunology, 2024)
During inflammation, human neutrophils engage β2-integrins to migrate from the blood circulation to inflammatory sites with high cytokine but low oxygen concentrations. We tested the hypothesis that the inhibition of prolyl hydroxylase domain-containing enzymes (PHDs), cytokines, and β2-integrins cooperates in HIF pathway activation in neutrophils. Using either the PHD inhibitor roxadustat (ROX) (pseudohypoxia) or normobaric hypoxia to stabilize HIF, we observed HIF1α protein accumulation in adherent neutrophils. Several inflammatory mediators did not induce HIF1α protein but provided additive or even synergistic signals (e.g., GM-CSF) under pseudohypoxic and hypoxic conditions. Importantly, and in contrast to adherent neutrophils, HIF1α protein expression was not detected in strictly suspended neutrophils despite PHD enzyme inhibition and the presence of inflammatory mediators. Blocking β2-integrins in adherent and activating β2-integrins in suspension neutrophils established the indispensability of β2-integrins for increasing HIF1α protein. Using GM-CSF as an example, increased HIF1α mRNA transcription via JAK2-STAT3 was necessary but not sufficient for HIF1α protein upregulation. Importantly, we found that β2-integrins led to HIF1α mRNA translation through the phosphorylation of the essential translation initiation factors eIF4E and 4EBP1. Finally, pseudohypoxic and hypoxic conditions inducing HIF1α consistently delayed apoptosis in adherent neutrophils on fibronectin under low serum concentrations. Pharmacological HIF1α inhibition reversed delayed apoptosis, supporting the importance of this pathway for neutrophil survival under conditions mimicking extravascular sites. We describe a novel β2-integrin-controlled mechanism of HIF1α stabilization in human neutrophils. Conceivably, this mechanism restricts HIF1α activation in response to hypoxia and pharmacological PHD enzyme inhibitors to neutrophils migrating toward inflammatory sites.